2016
DOI: 10.1161/atvbaha.115.306770
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Smooth Muscle Cell Dysfunction Under Diabetic Conditions by miR-504

Abstract: Objectives Diabetes accelerates pro-atherogenic and pro-inflammatory phenotype of VSMC associated with vascular complications. Evidence shows that microRNAs (miRNAs) play key roles in VSMC functions, but their role under diabetic conditions is unclear. We profiled miRNAs in VSMC from diabetic mice and examined their role in VSMC dysfunction. Approach and Results High throughput small RNA-sequencing identified 135 differentially expressed miRNAs in VSMC from type-2 diabetic db/db mice (db/dbVSMC) versus non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 75 publications
(78 reference statements)
6
61
0
Order By: Relevance
“…However, there is scant current knowledge about the role of miRNAs in VSMC dysfunction in diabetic vascular disease. Recently, it has been reported that DM misregulates miR-504, which promotes VSMC dysfunction in db/db mice with type 2 DM (T2DM) (17). However, it is likely that the detrimental diabetic phenotype of VSMCs in vasculoproliferative disease is mediated by multiple miRNAs whose contemporary dysregulation act together to alter the multifactorial vascular response in diabetes.…”
Section: Phenotypic Switch Of Vascular Smooth Muscle Cells (Vsmcs)mentioning
confidence: 99%
“…However, there is scant current knowledge about the role of miRNAs in VSMC dysfunction in diabetic vascular disease. Recently, it has been reported that DM misregulates miR-504, which promotes VSMC dysfunction in db/db mice with type 2 DM (T2DM) (17). However, it is likely that the detrimental diabetic phenotype of VSMCs in vasculoproliferative disease is mediated by multiple miRNAs whose contemporary dysregulation act together to alter the multifactorial vascular response in diabetes.…”
Section: Phenotypic Switch Of Vascular Smooth Muscle Cells (Vsmcs)mentioning
confidence: 99%
“…9 Reddy and colleagues showed that 135 miRNAs were differentially regulated in SMC cultured from thoracic aortas from diabetic db/db mice, as compared to SMC cultured from non-diabetic db/+ controls. The diabetes-induced increases in miR504 levels were further validated, and overexpression of miR504 was demonstrated to stimulate proliferation and migration of SMC.…”
Section: Novel Pathways For Vascular Cell Perturbations In Diabetesmentioning
confidence: 99%
“…Rather, their best characterized function is as modulators of voltage-gated Na + channels (Na V s) (9), and mutations that affect their Na V modulatory ability have been identified in cardiac arrhythmias and neurologic diseases such as Brugada syndrome, autosomal dominant cerebral ataxia, and epilepsy (10)(11)(12). Beyond regulation of Na V s, FGF13, encoded by Fgf13 on the X chromosome, can regulate other voltage-gated ion channels (13,14) and appears to affect a number of other cellular processes and contribute to physiology or disease states, including cancer (15), hypertrichosis (16), smooth and skeletal muscle cell development (17,18), microtubule stabilization in developing neurons (19), and protection from mechanical stress in cardiomyocytes by regulation of caveolae (20). These observations suggest that the full complement of FGF13 functions is not fully defined.…”
mentioning
confidence: 99%